2005
DOI: 10.1088/0741-3335/47/8/009
|View full text |Cite
|
Sign up to set email alerts
|

The first results of O-ICR experiments to remove re-deposited layers and hydrogen in the HT-7 superconducting tokamak

Abstract: Oxidation experiments associated with ion cyclotron resonance discharges (O-ICR) have been performed in HT-7 in the presence of a permanent magnetic field of 1.5-2.0 T. The influence of ICRH power and filling pressure on hydrogen and carbon removal rates was analysed. Total numbers of 5.70 × 10 22 H-atoms, 1.6 × 10 22 D-atoms and 2.35 × 10 22 C-atoms had been removed within eight O-ICR cleanings. An ∼20.5 nm co-deposited film on average was removed from the limiters and liners with an area of 12 m 2 . About 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…Among these techniques, oxygen glow discharge cleaning was proven as one promising candidate to remove re-deposited layers. For example, ASDEX Upgrade showed that removal is very effective even at room temperature and similar results were obtained in TEXTOR and HT-7 for elevated temperatures [4][5][6][7][8]. Schwarz-Selinger et al [11,12] have recently shown that oxygen plasmas are very efficient for removal of hydrocarbon films which are a good model system for re-deposited carbon films in fusion devices.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Among these techniques, oxygen glow discharge cleaning was proven as one promising candidate to remove re-deposited layers. For example, ASDEX Upgrade showed that removal is very effective even at room temperature and similar results were obtained in TEXTOR and HT-7 for elevated temperatures [4][5][6][7][8]. Schwarz-Selinger et al [11,12] have recently shown that oxygen plasmas are very efficient for removal of hydrocarbon films which are a good model system for re-deposited carbon films in fusion devices.…”
Section: Introductionmentioning
confidence: 69%
“…To avoid continuous build-up of a fuel inventory inside the vacuum vessel, a variety of techniques for regular tritium removal have been proposed. These techniques include glow discharge cleaning [4][5][6][7][8], thermal oxidation [9] and laser and flash lamp ablation techniques [10]. Among these techniques, oxygen glow discharge cleaning was proven as one promising candidate to remove re-deposited layers.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon removal rates were determined by residual mass analysis of the exhaust gas and impressive cleaning rates could be extrapolated to ITER [395].…”
Section: Conditioning With Permanent Magnetic Fieldmentioning
confidence: 99%
“…Examples of applications are patterning processes in microelectronics fabrication [1][2][3], the removal of diffusionbarrier carbon coatings on polyethylene terephthalate bottles prior to recycling [4], and the cleaning of optical components in synchrotron beamlines [5]. More recently it has also attracted considerable attention for the removal of redeposited hydrocarbon films in magnetic-confinement nuclear fusion experiments [6][7][8][9][10][11][12].…”
mentioning
confidence: 99%